THE COMPARISON OF USING MIND MAPPING AND KNOWLEDGE MAPPING TECHNIQUE TOWARD STUDENTS’ READING COMPREHENSION IN REPORT TEXT AT THE ELEVENTH GRADE AT SMA N 1 TRIMURJO IN THE ACADEMIC YEAR 2015/2016 - Defy Gustianing; Hadiyan Muhammad Hariz (UAD TEFL International Conference)
The objectives of this research are to know whether there is a difference result of reading comprehension by using mind mapping and knowledge mapping technique or not and to know which one is more effective technique between mind mapping and knowledge mapping technique.This research is a quantitative research.The design of this research is pre test-post test control group design which employs two groups. Experimentgroup is treated by mind mapping technique and control class is treated by knowledge mapping technique. Then, the total population is 123 students at the eleventh grade of SMA N 1 Trimurjo. The researcher takes 40 students, 20 students as experiment and20 as control. In taking the sample, the researcher used total cluster random sampling.The result of ttest is 2,91 and ttable  is 2,02 (on criterion 1) and 2,70 (on criterion 2). It means that tcount>ttable. So, there is a difference result of reading comprehension by using mind mapping and knowledge mapping technique and reading comprehension by using mind mapping technique is more effective than knowledge mapping technique.